Polarization Behavior of Bone Macrophage as Well as Associated Osteoimmunity in Glucocorticoid-Induced Osteonecrosis of the Femoral Head - Zhang Q; Sun W; Li T; Liu F (Dove Medical Press, 2023)
Qingyu Zhang,1 Wei Sun,2,3 Tengqi Li,4,5 Fanxiao Liu1 1Department of Orthopaedics, Shandong Provincial Hospital Affiliated to Shandong First Medical University, Jinan, Shandong, People's Republic of China; 2Department of Orthopaedic Surgery, Perelman School of Medicine, University of Pennsylvania, Philadelphia, PA, USA; 3Centre for Osteonecrosis and Joint-Preserving & Reconstruction, Orthopaedic Department, China Japan Friendship Hospital, Beijing, 100029, People's Republic of China; 4Department of Orthopedics, Peking University Shougang Hospital, Beijing, People's Republic of China; 5Department of Orthopedics, Peking University China-Japan Friendship School of Clinical Medicine, Beijing, People's Republic of ChinaCorrespondence: Fanxiao Liu, Department of Orthopedics, Shandong Provincial Hospital Affiliated to Shandong First Medical University, Jinan, Shandong, People's Republic of China, Tel/Fax +86-531-68773195, Email woshi631@126.comAbstract: Glucocorticoid-induced osteonecrosis of the femoral head (GIONFH) is a disabling disease with high mortality in China but the detailed molecular and cellular mechanisms remain to be investigated. Macrophages are considered the key cells in osteoimmunology, and the cross-talk between bone macrophages and other cells in the microenvironment is involved in maintaining bone homeostasis. M1 polarized macrophages launch a chronic inflammatory response and secrete a broad spectrum of cytokines (eg, TNF-α, IL-6 and IL-1β) and chemokines to initiate a chronic inflammatory state in GIONFH. M2 macrophage is the alternatively activated anti-inflammatory type distributed mainly in the perivascular area of the necrotic femoral head. In the development of GIONFH, injured bone vascular endothelial cells and necrotic bone activate the TLR4/NF-κB signal pathway, promote dimerization of PKM2 and subsequently enhance the production of HIF-1, inducing metabolic transformation of macrophage to the M1 phenotype. Considering these findings, putative interventions by local chemokine regulation to correct the imbalance between M1/M2 polarized macrophages by switching macrophages to an M2 phenotype, or inhibiting the adoption of an M1 phenotype appear to be plausible regimens for preventing or intervening GIONFH in the early stage. However, these results were mainly obtained by in vitro tissue or experimental animal model. Further studies to completely elucidate the alterations of the M1/M2 macrophage polarization and functions of macrophages in glucocorticoid-induced osteonecrosis of the femoral head are imperative.Keywords: osteonecrosis, macrophage polarization, osteoimmunity, osteoclast differentiation, osteogenesis, glucocorticoid